PERFORMANCE OF FILTERS INCORPORATED BY PARCHMENT COFFEE GRAIN IN SEWAGE TREATMENT PROCESSING OF FRUITS OF COFFEE - Lo Monaco, Paola Alfonsa Vieira; Matos, Antonio Teixeira de; Eustáquio Júnior, Valdeir; Sarmento, Antover Panazzolo; Moreira, Raphael Magalhães Gomes (Coffee Science - ISSN 1984-3909, 2011)
It was evaluated the performance of an organic filter using parchment coffee beans filter material in the primary treatment of wastewater from hydraulic separation and peeling of the fruits of coffee (ARC). Each 2000 L filtered ARC were measured in the effluent of organic filters, electrical conductivity (EC) and hydrogen potential (pH), and quantified the concentrations of total solids (ST), dissolved (SDT), suspended (SST), fixed (SFT) and volatile (SVT), total nitrogen (N-total), total phosphorus (P-total), total potassium (K-total) and sodium (Na). 12 screens were carried ARC area, calculated as the ratio of effluent concentration relative to influent concentration. According to the results obtained, we can conclude that the filter consists of parchment coffee beans was not efficient in the removal of EC, ST, SST, SDT, SFT, SVT, N-total, P-total and K-total, and has also contributed to the increase in effluent concentrations of these variables, however was relatively efficient in removing TSS and Na, with an average removal of 60% and 22%, respectively.